Topological conjugacies of piecewise monotone interval maps - Nikos A. Fotiades; Moses A. Boudourides (International Journal of Mathematics and Mathematical Sciences)
Our aim is to establish the topological conjugacy between piecewise monotone expansive interval maps and piecewise linear maps. First, we are concerned with maps satisfying a Markov condition and next with those admitting a certain countable partition. Finally, we compute the topological entropy in the Markov case.